Challenges and Solutions in the Implementation of the Family Hope Program - Khabibi, Akhmad; Rodiyah, Isnaini (Indonesian Journal of Cultural and Community Development, 2024)
The general background family Hope Program (PKH) represents a significant initiative aimed at reducing poverty through conditional cash transfers to very poor households, initiated in 2007. Specific background however, while many countries have adopted similar strategies, the effective implementation of such programs in rural contexts often faces numerous challenges. Knowledge gap This study specifically investigates the implementation of PKH in Gempol Village, addressing the knowledge gap regarding community attitudes and the practical obstacles that impede program success. Aims aim of this research is to analyze the barriers faced by stakeholders and participants in the execution of PKH. Results Findings reveal that successful implementation depends on enhanced coordination among government officials, program coordinators, and beneficiaries, as well as the necessity for ongoing education to ensure participants comprehend the requirements for enrollment in the program.The novelty of this research lies in its focus on financial management skills, which are often overlooked but crucial for effective fund utilization among beneficiaries.The implications of this study underscore the importance of strengthening communication among stakeholders and providing targeted educational interventions, ultimately contributing to the sustainability and effectiveness of the PKH initiative and similar community development programs in rural settings. Highlights: Coordination between stakeholders is crucial for successful program execution. Continuous education is needed for participants to understand requirements. Financial management skills are essential for effective fund utilization. Keywords: Family Hope Program, Implementation, Challenges, Solutions, Community